Simulating the Formation of Composite Surface Structure during Electron Beam Treatment; Advanced Materials Research : Advanced materials, synthesis, development and application; Vol. 880 : Prospects of Fundamental Sciences Development (PFSD-2013) - Kryukova O. N. (Chemistry and Physics of Materials Surface, 2014)
Title screen